2006
DOI: 10.1167/iovs.05-0469
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries and Visual Field Summaries as Predictors of Glaucoma in the Ocular Hypertension Treatment Study

Abstract: The MP index, IOP asymmetry, and binocular test point asymmetry can assist in clinical evaluation of eyes at risk of development of POAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 12 publications
1
34
0
Order By: Relevance
“…In agreement with these data, a predictive value of asymmetry between eyes in OHT patients for the development of POAG has been already reported for IOP, 45 cup-to-disc ratio, 5 and VF threshold. 45 Although several HRT II parameters showed predictive ability, rim volume, C/D ratio, and mean RNFL thickness showed the best performance. These results are in accordance with the CSLO ancillary study of the OHTS, demonstrating that several baseline HRT parameters can be used to predict the development of POAG in OHT patients.…”
Section: Discussionsupporting
confidence: 79%
“…In agreement with these data, a predictive value of asymmetry between eyes in OHT patients for the development of POAG has been already reported for IOP, 45 cup-to-disc ratio, 5 and VF threshold. 45 Although several HRT II parameters showed predictive ability, rim volume, C/D ratio, and mean RNFL thickness showed the best performance. These results are in accordance with the CSLO ancillary study of the OHTS, demonstrating that several baseline HRT parameters can be used to predict the development of POAG in OHT patients.…”
Section: Discussionsupporting
confidence: 79%
“…This finding may correspond with prior studies reporting that when asymmetric IOP is present, the eye with the higher IOP may demonstrate greater glaucomatous damage. 16 Although the raw DCT-IOP difference was relatively small (0.8 mm Hg) between the paired eyes and there are many non-IOP influences on glaucoma severity, this finding is nonetheless compelling in its implication that DCT-IOP is better associated with the glaucomatous disease process than is GAT-IOP.…”
Section: Discussionmentioning
confidence: 95%
“…Our results are consistent with previous studies, which have indicated that asymmetry of IOP is a common finding in patients with glaucoma. [1][2][3][4][5][6] We have further demonstrated that the likelihood of having POAG increases as intereye IOP asymmetry increases. This seems to be a definite finding, leading to the conclusion that patients with an IOP difference of Z6 mm Hg should be considered as great risk for having glaucoma, whereas those with symmetric pressures are not likely to have the disease.…”
Section: Discussionmentioning
confidence: 99%